Subjective experience of aberrant salience in young people at Ultra-High Risk (UHR) for psychosis: a cross-sectional study. (1st February 2022) - Poletti, Michele; Pelizza, Lorenzo; Azzali, Silvia; Garlassi, Sara; Scazza, Ilaria; Paterlini, Federica; Chiri, Luigi Rocco; Pupo, Simona; Raballo, Andrea
Abstract: Purpose: Aberrant salience (AS) is conceptualized as a potential predisposing factor for psychotic states of mind. Despite several studies in the general population, research on AS in the early phases of psychosis is still relatively scarce. The aim of this cross-sectional study is (1) to evaluate the AS subjective experience in Ultra-High Risk (UHR) adolescents and young adults compared to help-seeking peers with First Episode Psychosis (FEP) and (2) to assess any significant association of baseline AS with psychopathology and functioning in UHR participants. Materials and methods: Participants (87 UHR and 139 FEP), aged 13–35 years, completed the Comprehensive Assessment of At-Risk Mental States (CAARMS), the Aberrant Salience Inventory (ASI) and the brief version of the Schizotypal Personality Questionnaire (SPQ-B). Within the UHR subgroup, Spearman correlation and multiple linear regression analyses among psychopathological parameters were performed. Results: No difference in baseline AS subjective levels was found between UHR and FEP participants (median [interquartile range]: 14.50 [7–19] vs 14 [9–21]; z = −1.576; p  = 0.115). In UHR individuals, the ASI total score was significantly associated with attenuated positive symptoms ( ρ  = 0.284, p  = 0.008), depression ( ρ  = 0.256; p  = 0.018) and specific schizotypal personality traits (i.e. cognitive-perceptual deficits and disorganization [respectively, ρ  = 0.487, p  = 0.001, and ρ  = 0.295, p  = 0.008]). Conclusions: AS is clinically relevant in UHR subjects, comparable to FEP patients. Moreover, it seems to mutually interact with schizotypy in the clinical manifestation of attenuated positive psychopathology.